Ivan Franko and His Community - Hrytsak, Yaroslav (Ukrainian Studies, 2019)
In this Ukrainian bestseller, now available in English for the first time, Yaroslav Hrytsak examines the first three decades (1856-86) in the life of Ivan Franko, a prominent writer, scholar, journalist, and political activist who became an indisputable leader in the forging of modern Ukrainian national identity. Hrytsak does so against the background of small communities--Franko's family, his native village, his colleagues, the editors of periodicals for which he worked, and the revolutionary circles with which he interacted--during a time when multi-ethnic Habsburg Galicia evolved into several modern nations. This volume will remain a recognized standard for the study of the history of Ukraine and East Central Europe.